PENGARUH SUASANA TOKO, HARGA, DAN KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN PADA COFFEE SHOP DI BANDAR LAMPUNG - Siti Widiyaningsih; May Roni; Ahmad Rifa'i; Fira Agustina (Jurusan Administrasi Bisnis, FISIP, Universitas Lampung, 2026)
Modern lifestyle changes have shifted the meaning of drinking coffee from a mere routine activity into a part of urban culture and social identity. Bandar Lampung, which has great potential as a center of the creative economy and one of Indonesia’s main Robusta coffee-producing regions, provides a promising environment for the coffee industry. This study aims to analyze the influence of store atmosphere, price, and service quality on customer satisfaction at Coffee Shop Nuju Coffee. This research uses a quantitative approach with a non-probability sampling method and purposive sampling technique, targeting consumers of Coffee Shop Nuju Coffee as the research subjects. The sample size was determined using Cochran’s formula, resulting in 96 respondents. Data werecollected through questionnaires and analyzed using descriptive statistics and multiple regression with the assistance of SPSS 27.0 software. The analytical techniques included instrument testing and hypothesis testing. The results show that store atmosphere, price, and service quality simultaneously have a significant effect on customer satisfaction, and each variable also has a partial influence on customer satisfaction at Coffee Shop Nuju Coffee.